A Case of Bilateral Extracranial Internal Carotid Artery Dissection Due to the Helmet Strap After Motorcycle Crash. (June 2019) - Gioia, Sara; Franceschetto, Lisa; Lancia, Massimo; Bacci, Mauro; Suadoni, Fabio
Abstract : Abstract: The authors report a case of a man who developed stroke symptoms a few days after a road accident on his motorcycle. Radiographic examinations revealed the presence of bilateral dissection of the extracranial internal carotid arteries with signs of involvement of the brain parenchyma. The location, timing, and presentation lead to the conclusion that the carotid lesions were secondary to the motorcycle collision; in particular, we suppose that it is due to the pressure exerted by the helmet strap worn. Although helmets have undoubtedly prevented serious injuries, this report highlights that the helmets themselves may cause injuries, especially to cervical soft tissues and vessels.